Análisis de vulnerabilidad MS17-010 en entornos empresariales. - Cerezo Bravo, Stalin Javier (2024)
For countries and organizations to function, it is essential to have sufficient cybersecurity to protect data networks and the information passing through them from the risk of cyber attacks. The introduction of new digital technologies, together with the growing dependence on them, creates a fragile environment that cannot be ignored for the correct functioning of various functions in organizations, becoming a potential threat to national sovereignty. The appearance of the WannaCry ransomware at the beginning of May 2017 marked a milestone in cybersecurity, impressing companies or organizations worldwide, generating a series of conflicts and economic losses. The central part of this attack lies in the exploitation of the MS17-010 vulnerability in Windows operating systems, showing the vulnerabilities related to the cybersecurity management of companies.